2022
DOI: 10.1002/advs.202105868
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Aggregation Induced Immunogenic Rupture (PAIIR)

Abstract: Immunogenic cell death (ICD) arises when cells are under stress, and their membranes are damaged. They release damage‐associated molecular patterns (DAMPs) that stimulate and drive the type and magnitude of the immune response. In the presence of an antigen, DAMPs ride the longevity and efficacy of antigen‐specific immunity. Yet, no tool can induce the controlled ICD with predictable results. A peptide‐based tool, [II], is designed that aggregates in the cell and causes cell membrane damage, generates ICD and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 76 publications
2
20
0
Order By: Relevance
“…0.2 w% albumin) as shown before. 18 During 3 h of treatment, [II] in 0 w% (without albumin) did not cause any membrane damage (Figure 3B), as…”
Section: The Effect Of Enhanced Lipid Membrane Accumulation Ofmentioning
confidence: 72%
See 2 more Smart Citations
“…0.2 w% albumin) as shown before. 18 During 3 h of treatment, [II] in 0 w% (without albumin) did not cause any membrane damage (Figure 3B), as…”
Section: The Effect Of Enhanced Lipid Membrane Accumulation Ofmentioning
confidence: 72%
“…0.2w% albumin) as shown before. 12 During 3h of treatment, [II] in 0 w% (without albumin) did not cause any membrane damage (Figure 3B), as [II] fibrils do not interact with the lipid membrane (Figure 1B). Addition of [II] with 0.2 w% albumin showed increasing membrane damage over time which is quantified by the release of lactate dehydrogenase (LDH), a cytoplasmic enzyme released upon membrane damage.…”
Section: Delayed Aggregation Increased the Lipid Membrane Integration...mentioning
confidence: 95%
See 1 more Smart Citation
“…40,41 We previously showed that [II] aggregation-induced cell death is ICD through the release of DAMPs in multiple cell lines. 12 Given that eIF2α phosphorylation results in calreticulin surface localization, we identified the localization of calreticulin within the cells incubated with [II]. Cal-reticulin was observed only intracellularly in control cells and cells treated with 0.5mM [II] in 0% albumin.…”
Section: Resultsmentioning
confidence: 99%
“…On the cell membrane, [II] peptide-aggregation induces immunogenic rupture (PAIIR) that initiates immunogenic cell death (ICD) and associated release of damage associated molecular patterns (DAMPs) as an immunostimulatory tool. 12 PAIIR induces secondary pyroptosis, a programmed ICD and a common feature of amyloid inducing cell death as in Alzheimer’s and Parkinson’s diseases. 13,14 PAIIR is a simplified peptide-based tool, designed to mimic the function, instead of the sequence of a protein; thus there is no natural ortholog of [II].…”
Section: Introductionmentioning
confidence: 99%